Synthesis and Biological Profiling of Seven Heparin and Heparan Sulphate Analogue Trisaccharides - Fruzsina Demeter; Zsófia Peleskei; Katalin Kútvölgyi; Ágnes Rusznyák; Ferenc Fenyvesi; Richárd Kajtár; Éva Sipos; István Lekli; Petra Molnár; Attila Gábor Szöllősi; Erika Lisztes; Balázs István Tóth; et al. (Biomolecules)
Researchers are paying increasing attention to the strongly negatively charged heteropolysaccharides in cells, in the extracellular matrix or in the cell wall. Examples of such molecules are glycosaminoglycans (e.g., heparin, heparan sulphate). It is well known from the literature that heparin and its derivatives have anti-inflammatory, angiogenic, metastatic and growth factor inhibitory activity. Herein, we present the efficient synthesis of six non-glycosaminoglycan (Glc-GlcA-Glc-sequenced) and one heparin-related (GlcN-GlcA-Glc-sequenced) trisaccharides with various functional group patterns. The anti-inflammatory, antioxidant and cell growth-inhibitory/cytotoxic effects of the synthesized compounds were tested. Among the investigated molecules, we have found some derivatives with a promising anti-inflammatory and antioxidant effect.